2017
DOI: 10.1590/1982-0194201700006
|View full text |Cite
|
Sign up to set email alerts
|

Carga de trabalho de enfermagem relacionada ao índice de massa corporal de pacientes críticos

Abstract: Objective: To measure and compare the nursing workload and the frequency of the items scored in the Nursing Activities Score (NAS) considering the different groups of BMI of patients hospitalized in Intensive Care Units (ICU). Methods: Longitudinal study conducted in the ICU of a university hospital in São Paulo in which the BMI of patients was calculated by dividing the weight by the square of the height and the nursing workload was measured through the NAS. Results: Analysis of 529 patients showed that the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 12 publications
0
6
0
10
Order By: Relevance
“…Quanto ao cuidado dispensado ao paciente obeso, estudo aponta que gera sobrecarga especialmente nos cuidados de higiene, mudança de decúbito, pois precisaram ser realizados com três ou mais profissionais. Contudo, os pacientes obesos não geram necessariamente um aumento na carga de trabalho em relação à horas de trabalho, mas sim implica em maior quantitativo de profissionais, devido à dificuldade de mobilização no leito, demandando Sendo assim, o número reduzido de profissionais de enfermagem pode favorecer um aumento de eventos adversos (Goulart, et al, 2017), como LPP.…”
Section: Discussionunclassified
“…Quanto ao cuidado dispensado ao paciente obeso, estudo aponta que gera sobrecarga especialmente nos cuidados de higiene, mudança de decúbito, pois precisaram ser realizados com três ou mais profissionais. Contudo, os pacientes obesos não geram necessariamente um aumento na carga de trabalho em relação à horas de trabalho, mas sim implica em maior quantitativo de profissionais, devido à dificuldade de mobilização no leito, demandando Sendo assim, o número reduzido de profissionais de enfermagem pode favorecer um aumento de eventos adversos (Goulart, et al, 2017), como LPP.…”
Section: Discussionunclassified
“…Conversely, one Brazilian study compared ICU nursing workload across patient's BMI categories, and found that although nursing workload was not different for patients with and without obesity (p = .219), patients with severe obesity (BMI ≥40) required a significantly higher nursing workload compared to patients with less severe obesity (BMI 30-34.9 and 35-39.9) (p = .004) (Carrara et al, 2016). Further analysis found that for patients with obesity, nursing workload was significantly increased in delivering patient hygiene for more than 2 hours per shift (p =.037); and mobilisation and repositioning requiring three or more nursing staff (p = .007) (Goulart et al, 2017). However, the authors advice against extrapolation of their findings, as the numbers analysed was low (6 patients with obesity, compared to 2 patients without obesity) and insufficiently powered to affirm increased nursing workload for patient mobilisation.…”
Section: Patient Characteristicsmentioning
confidence: 98%
“…Longer nursing time may be required for comprehensive physical assessment, nursing diagnoses and interventions. Examples of difficulties encountered with care of patients with obesity include repositioning of patients, for example, for physical assessment, wound care and pressure injury prevention (Drake et al, 2005;Goulart et al, 2017;Kam & Taylor, 2010;Lumley et al, 2015;Robstad et al, 2018;Shea & Gagnon, 2015;Tanaka & De Cássia Giani Peniche, 2009); increased time and nursing skill needed in managing impediments, such as excess adiposity, to physical examination (Drake et al, 2005;Singh et al, 2007), intravenous cannulation and venepuncture (Brannam et al, 2004;Kam & Taylor, 2010;Ngui et al, 2013;Sebbane et al, 2013;Shea & Gagnon, 2015;Singh et al, 2007;Winkelman & Maloney, 2005), and medication adjustment (Kam & Taylor, 2010;Shea & Gagnon, 2015); and increased time or attention to provide hygiene care, with regard to manual handling, cleaning of skin folds and extremities, and patient redressing (Bradway et al, 2010;Davidson & Callery, 2001;Drake et al, 2005;Goulart et al, 2017;Holland et al, 2001;Kam & Taylor, 2010;Winkelman & Maloney, 2005).…”
Section: Nursing Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Neste contexto, destaca-se a importância da quantificação da carga de trabalho, que dará apoio à adequação da equipa de enfermagem em relação às necessidades dos doentes. Ao identificar as características do serviço, contribuirá para a melhoria da qualidade dos cuidados prestados, preservando a saúde e segurança dos doentes, bem como dos trabalhadores (Goulart, Carrara, Zanei, & Whitaker, 2017). Nesta perspetiva, a carga de trabalho consiste no produto da média diária dos doentes assistidos, de acordo com o grau de dependência e o tipo de cuidados, pelo tempo médio de cuidados de enfermagem utilizados pelo doente de acordo com o grau de dependência e cuidados prestados (Fugulin, Gaidzinski, & Castilho, 2010).…”
unclassified